The Relationship Between Religion And Magic in Ancient Egypt - Rese. Elaf Safaa Naeem Karam; Dr.Fadhel Kadhem Hannoon (Journal of College of Education, 2025)
There is no dispute that religion was the dominant force in the emotions of the Pharaonic Egyptian people. Initially, the individual would supplicate to his god to ward off evil or reward him with good. At the same time, however, he would seek to fulfill his needs through methods more powerful and effective than those of the god he worshipped. Thus, matters became increasingly confused. We find that man recognized that, at all times and in all places, he was surrounded by hidden forces beyond his understanding. Therefore, he attempted to entice these forces through supplication, sometimes through art, at other times. In reality, religion and magic were the offspring of this dual human effort, and it became natural for them to intersect at several points. In times of misery, the ancient Egyptian often turned to his gods in supplication or fear, desire or awe. If he was unable to achieve what he desired, he resorted to magic, which controlled even the gods. The most important themes of this study were spells and amulets, magical rituals, astrology, and dreams.